Advances in Parasitic Weeds Research - Hanan Eizenberg (Frontiers Research Topics, 2018)
Parasitic weeds are severe constraint to agriculture and major crop production, and the efficacy of available means to control them is minimal. Control strategies have centred around agronomic practices, resistant varieties and the use of herbicides. Novel integrated control programmes should be sympathetic to agricultural extensification while exerting minimal harmful effects on the environment. This eBook covers recent advances in biology, physiology of parasitism, genetics, population dynamics, resistance, host-parasite relationships, regulation of seed germination, etc., in order to offer an outstanding windows to these enigmatic plants, and contribute to their practical management.